American Economic Review. (Princeton, N.J. American Economic Association, 1911)
It contains a number of articles and shorter papers on economic subjects. The May issue presents the papers and proceedings of the previous year‟s annual meeting. Selected papers and discussions of papers presented at the meetings are published along with reports of officers, committees, and representatives.
Bimonthly
Full texts available at JSTOR and Proquest.
Keywords: Economics -- Periodical